2010
DOI: 10.3171/2010.8.peds10222
|View full text |Cite|
|
Sign up to set email alerts
|

Analysis of therapeutic choices for slit ventricle syndrome after cyst-peritoneal shunting for temporal arachnoid cysts in children

Abstract: Object The goal in this study was to investigate early diagnostic evidence, optimal therapeutic strategies, and prophylactic methods for slit ventricle syndrome (SVS) in patients with temporal lobe arachnoid cysts who received cyst-peritoneal (CP) shunts. Methods Six cases of SVS in patients with temporal lobe arachnoid cysts who received CP shunts were treated by the senior authors in 2 institutions bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Necropsy and histopathological examination showed epidural haematoma leading to transtentorial herniation and a collapsed, empty AC. CP shunt placement is a widely performed surgical method to treat temporal AC in human medicine (Fang et al, 2010). Shunting had a higher success rate than fenestration (Ciricillo et al, 1991;Satyarthee et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Necropsy and histopathological examination showed epidural haematoma leading to transtentorial herniation and a collapsed, empty AC. CP shunt placement is a widely performed surgical method to treat temporal AC in human medicine (Fang et al, 2010). Shunting had a higher success rate than fenestration (Ciricillo et al, 1991;Satyarthee et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Many other authors found the similar location as well. 9,10 The preference of the middle fossa location of the cysts reported for shunt dependency might be related to the local anatomical characteristics or the prevalence of the middle fossa location of arachnoid cysts. 11,12 Shunt dependency syndrome is usually presented with symptoms of intermittently increased ICP, including headache, vomiting, nausea, dizziness, and neurological deficits.…”
Section: Discussionmentioning
confidence: 99%
“…13 The proposed pathogenesis of the syndrome included the collapsed cyst wall obstructing the shunt proximal catheter and progressive decreased cerebral compliance because of fibrosis. 9,15 Regression of CSF absorption after shunt might also be involved. 16 Our intraoperation observation was supportive of the catheter obstruction theory and stood for our procedures to remove the collapsed and thickened cyst wall.…”
Section: Discussionmentioning
confidence: 99%